Evidence from the BRICS Nations on Empirical links between ICT, Tourism, and Commerce in the Pursuit of a Sustainable Environment (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Information and communication technology (ICT) sustainability is a topic of vigorous andsophisticated academic discussion. Utilizing the Environmental Kuznets curve (EKC) theory, this studyexamines whether technology for communication and information, economic expansion, and financialgrowth affect carbon dioxide emission in the BRICS countries. The Methods for Moments - QuantileAnalysis was used to do this, and the outcomes indicate that the impact of the variables that explained theresults varied according to the quantile of CO2 emission. The overall findings indicates that, butinformation and communication technology (ICT) mostly reduces emissions at lower emission quantiles,economic expansion and financial growth increase the amount of CO2. It studies that match the EKChypothesis along with it. It's noteworthy to see that the amount of the effects of information andcommunication technology and economic growth on carbon dioxide emissions are smaller. The findingsof the causality test demonstrate that any policy change influencing the explanatory variables has asignificant influence on carbon dioxide emissions and vice versa, demonstrating bidirectional causationbetween the model parameters. Policymakers may now build a framework for accomplishing theSustainable Development Goals based on the findings.